Prize and Risk-Taking Strategy in Tournaments : Evidence from Professional Poker Players - Jungmin Lee (Institute for the Study of Labor (IZA), 2004)
This study examines whether people optimally respond to prize incentives for risk taking in tournaments. I exploit the television game show World Poker Tour as a natural experiment. The results show that professional players strategically choose the degree of risk taking depending on the incentives implied by the prize structure they face. I find that they are more sensitive to losses than to gains.
Keywords: M5; D8; 330; risk; tournament; poker; Risikopräferenz; Glücksspiel; Wettbewerb; Preis; Ökonomischer Anreiz; Experiment